The Aboriginal Adjustment Movement in Colonial Victoria - Cahir, Fred (Journal of religious history, 2019)
Whilst much has been written about Aboriginal religious syncretism in Australia, particularly about what has become known as the "Adjustment Movement" that occurred in Arnhem Land in the 1950s (see McIntosh 2004), there were several remarkable examples of spiritual adjustment by Aboriginal people a century earlier on the Victorian goldfields that hitherto have not been explored by historians. Building on Magowan's (2003) discussion of the connection between Christianity and the ancestral law of Aboriginal culture in northern Australia, this article will examine how Christian influences in colonial Victoria competed with, and conversely moulded, southern Kulin ancestral understanding. Several Kulin ceremonies — including the Myndee ceremony and the "Veinie Sacred Sunday Dance" — will be examined. These ceremonies were described by colonial officials (Joseph Panton, a Gold Commissioner, and William Thomas, the Aboriginal Guardian of Aborigines in Victoria) in the midst of a second wave of invasion and rupture for Victorian Aboriginal people — the first being the sheep herders in the 1830s, and the second being the gold rush which commenced in 1851. Serving as exemplars of what might be called the Victorian Aboriginal Adjustment Movement, these ceremonies demonstrate the extent to which Aboriginal people on the goldfields of Victoria engaged in a culturally congruent mode of Christianity.